Characterization of Aquaporin 4 Protein Expression and Localization in Tissues of the Dogfish (Squalus acanthias) - Cutler, Christopher P.; Harmon, Sheena; Walsh, Jonathon; Burch, Kia (Frontiers in Physiology, 2012)
The role of aquaporin water channels in Elasmobanchs such as the dogfish Squalus acanthias is completely unknown. This investigation determines the expression and cellular and sub-cellular localization of AQP4 protein in dogfish tissues. Two polyclonal antibodies were generated (AQP4/1 and AQP4/2). Western blots using the AQP4/1 antibody showed two bands (35.5kDa and 49.5kDa) in most tissues similar to mammals. Liver and rectal gland showed further bands. However, unlike in mammals, AQP4 protein was expressed in all tissues including respiratory tract and liver. The AQP4/2 antibody appeared much less specific in blots. Both antibodies were used in immunohistochemistry and showed similar cellular localizations, although the AQP4/2 antibody had a more restricted sub-cellular distribution compared to AQP4/1 and therefore appeared to be more specific. In kidney a sub-set of tubules were stained which may represent intermediate tubule segments. AQP4/1 and AQP4/2 antibodies localized to the same tubules segments in serial sections although the intensity and sub-cellular distribution were different. AQP4/2 showed a basal or basolateral membrane distribution whereas AQP4/1 was often distributed throughout the cell including the nucleus. In rectal gland and cardiac stomach AQP4 was localized to secretary tubules but again AQP/1 and AQP/2 showed different sub-cellular distributions. In gill, both antibodies stained large cells in the primary filament and secondary lamellae. Again AQP4/1 antibody stained most or all the cell including the nucleus, whereas AQP4/2 had a plasma membrane and sometimes cytoplasmic distribution. Two types of large mitochondria-rich cells are known to exist in elasmobranches, that express either Na,K ATPase or V-type ATPase. Using Na,K-ATPase and V-type ATPase antibodies, AQP4 was colocalized with these proteins using the AQP4/1 antibody. Results show AQP4 is expressed in both (and all) branchial Na,K ATPase and V-type ATPase expressing cells.